Debate: Forced Labour, Slavery and Human Trafficking: When do definitions matter? - Plant, Roger (Anti-Trafficking Review, 2015)
We can spend a lot of time debating the connections or essential differences between the concepts of trafficking, forced labour, slavery and modern slavery, or slavery-like practices. Some insist that trafficking is a subset of forced labour, others the reverse. The arguments between academics, bureaucracies and even government agencies have often been vitriolic.